KEBUTUHAN PESERTA DIDIK DAN RANCANG BANGUN MEDIA PEMBELAJARAN BAHASA ARAB DI MADRASAH ALIYAH - Gazali, Erfan; Saefuloh, Hasan (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2019)
This study aimed to map the Arabic learning needs of Islamic senior high school students (Madrasah Aliyah) in the Cirebon city and Cirebon regencies. This research is the first and second stage of the four stages of the 'Four Door' (4D) research model. The 4D research model has four stages: (1) Defining, (2) Design, (3) Developing, and (3) Disseminating. The